2014
DOI: 10.1111/pcn.12152
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and mental health problems in patients with thalidomide embryopathy in Japan

Abstract: Aim:The aim of the study was to examine the presence of psychological and mental health problems in patients with thalidomide embryopathy in Japan in order to develop and build future support systems. Methods:The present study examined the presence/ absence of electroencephalographic abnormalities, intellectual/cognitive functions, and mental health problems in 22 participants (nine men, 13 women) with thalidomide embryopathy. Participants completed the electroencephalograph instrument. Participants were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Some studies of the long-term outcome related to a variety of the malformations have recently been published—on ocular problems [10], speech pathology [11], oral health including teeth [12] and the development of degenerative changes to the lower limbs and the cervical spine [13, 14]. Studies from Japan report that mental health had deteriorated and anxiety levels had increased in this population [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies of the long-term outcome related to a variety of the malformations have recently been published—on ocular problems [10], speech pathology [11], oral health including teeth [12] and the development of degenerative changes to the lower limbs and the cervical spine [13, 14]. Studies from Japan report that mental health had deteriorated and anxiety levels had increased in this population [15]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent study by a Japanese group evaluated the psychological and mental health of TE individuals. It was concluded that despite there being no evident influence of thalidomide in encephalographic abnormalities, these individuals seem to have a decreased working memory capacity (Imai et al, ). They also observed that in TE individuals there is evidence of somatic suffering, such as anxiety and insomnia (Imai et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that despite there being no evident influence of thalidomide in encephalographic abnormalities, these individuals seem to have a decreased working memory capacity (Imai et al, ). They also observed that in TE individuals there is evidence of somatic suffering, such as anxiety and insomnia (Imai et al, ). Similar to our research, the group was only able to compare these conditions with a general population of individuals without congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one recent study focused mainly on lifestyle‐related diseases among middle‐aged thalidomiders (Shiga, Shimbo, & Yoshizawa, ), while a few others investigated internal organ and vascular anomalies using imaging screening (Tajima, Wada, & Yoshizawa, ; Weinrich et al, ). In addition, reports have been published on mental disorders and psychological problems in thalidomiders in Sweden and Japan (Ghassemi Jahani, Karlsson, et al, ; Imai et al, ), and on peripheral nerve dysfunction in thalidomiders in the UK (Nicotra et al, ). Moreover, in 2017, a practical guide was devised to aid understanding of and to discuss treatment for TE in all medical areas (Ohnishi & Hinoshita, in Japanese and 2018 in English).…”
Section: Introductionmentioning
confidence: 99%